INTRODUCTION TO ROKAT PAKARANGAN CULTURE THROUGH GUIDED LEARNING, READING, INTERPRETING, UNDERSTANDING AND APPLYING - Abd Azis; Agus Wahdian; Salamet Wahedi; Hodairiyah Hodairiyah; Siti Arifah (STKIP Paracendekia NW Sumbawa, 2024)
The object of introducing culture or tradition (rokat Pakarangan) is one of the natural riches that we should be proud of and grateful for. Every place in Sumenep has its own culture and traditions, and each culture or tradition has its uniqueness. Even though the Aeng Panas village government has declared Aeng Panas local culture or traditions as native regional culture, there are still no significant results because there are still many obstacles. Aeng Panas has many local cultures and traditions. However, many students and teenagers still need to learn about it through the Guided, Reading, Interpreting, Understanding, and Applying (DM4) learning approach or model. Many results were obtained. One of them is that the culture or traditions in Aeng Panas village will grow and continue to be preserved by teenagers or students for several years. The expected benefits of this research are that it can help the local village government introduce the culture or tradition of Rokat Pakarangan to achieve the goal of teaching and preserving it. The method used in this research is a survey method to carry out observations and studies. The result of this research is to know the introduction of the culture or traditions of the Aeng Panas rokat Pakarangan through a guided learning approach or model, reading, interpreting, understanding and applying (DM4).